Portrait of pain: Photographic coverage of crime and accident reports in Spanish newspapers (1977-2000) - Marauri Castillo, Iñigo; Rodríguez González, Mª del Marq; Cantalapiedra González, Mª José (Estudios sobre el Mensaje Periodístico, 2012)
The evolution in design of newspapers during the last 25 years of twentieth century has turned photography into one of the most important elements of the press coverage. The technical advances in printing and publishing, together with the powerful influence of television, have cemented its rising importance. Within this change, accident and crime reports, far from being an exception, have become one of the cutting-edge areas. This is confirmed in this article, which analyses the evolution of photographic view in the Spanish quality newspapers (El País, Abc, El Mundo, Diario 16, La Vanguardia de Barcelona, El Periódico de Catalunya and El Correo Español-El Pueblo Vasco) in their coverage of eleven of the main big accidents, natural disasters and crimes that occurred in Spain between 1977 and 2000.
Keywords: Crime and accident reports; photography; pain; tragedy.